834 ➗ 2 =417. I hope I helped :)
Answer:
Step-by-step explanation:
Rearrange each function to solve for x.
Switch x and y,
The resulting equation is the inverse function.
A:
f(x) = y = 5+x
x = y-5
y = x-5
f⁻¹(x) = x-5
g(x) = 5-x ≠ f⁻¹(x)
g(x) is not the inverse of f(x).
:::::
B:
f(x) = y = 2x-9
x = (y+9)/2
y = (x+9)/2
f⁻¹(x) = (x+9)/2
g(x) = (x+9)/2 = f⁻¹(x)
g(x) is the inverse of f(x).
:::::
C:
f(x) = y = 2/x - 6
x = 2/(y+6)
y = 2/(x+6)
f⁻¹(x) = 2/(x+6)
g(x) = (x+6)/2 ≠ f⁻¹(x)
:::::
D:
f(x) = y = x/3 + 4
x = 3y - 12
y = 3x - 12
f⁻¹(x) = 3x - 12
g(x) = 3x - 4 ≠ f⁻¹(x)
g(x) is not the inverse of f(x).
Answer:
-|x|=-3
|x|=-3
|-x|=-3
Step-by-step explanation:
Answer:
True
When you add two negative numbers the sum is always negative ex.
When you add two numbers with different signs get the difference and get the sign by the larger absolute value ex.
Step-by-step explanation:
You would call them <span>Ice Queen Clones</span>